AB0586 Short and Long-Term Anti-TNF-Alpha Therapy in Refractory Uveitis. Study of 40 Adult Patients from A Single Universitary Center. (10th June 2014) - Ortiz-Sanjuán, F.M.; Calvo-Río, V.; Blanco, R.; Cañal-Villanueva, J.; Ventosa, J.; Loricera, J.; Santos-Gόmez, M.; Pina, T.; González-Gay, M.A.
Abstract : Objectives: To assess the efficacy and safety of anti-TNFα drugs in refractory uveitis to conventional synthetic immunosuppressive drugs (CSISDs). Methods: Study of refractory uveitis from a single Universitary hospital who had failed to at least one CSISD. The degree of ocular inflammation was established according to SUN-2005. Macular thickness was evaluated by OCT. We compared data between baseline 1st month, and 1st, 2nd, 3rd and 4th year (Wilcoxon test). Results: We studied 40 adult patients/62 affected eyes (16 men/24 women); mean age, 39.3±11.5 years. The underlying pathologies were Spondyloarthritis-HLA-B27+ (n=7), Behçet disease (n=6), sarcoidosis (n=6), VKH (n=2), Birdshot (n=1), serpinginous (n=1), sympathic opthalmopathy (n=1), Juvenile Idiopathic Arthritis (n=1) and idiopathic uveitis (n=15). Besides oral corticosteroids and before anti-TNFα, patients had received methylprednisolone i.v. (n=9), methotrexate (n=16), cyclosporine A (n=13) and azathioprine (n=10). The first anti-TNFα was: adalimumab (n=18; 45%) (40 mg/sc/2 weeks) and infliximab (n=22; 55%) (5 mg/kg/i.v./every 4-8 weeks. Anti-TNFα drugs were used as monotherapy (n=8), or combined with methotrexate (n=18), azathioprine (n=10), Cyclosporine A (n=3) and salazopyrine (n=1). Adalimumab was switched to golimumab (50 mg/sc/week) (n=2) and to tocilizumab (n=2). Infliximab was switched to adalimumab (n=8) and to golimumab (n=2). Visual acuity (VA), Tyndall, vitritis and OCT experienced significant improvement at the 1st month, and 1st, 2nd and 3rd year. The mean OCT in cases of cystoid macular edema (OCT>300 μ) (n=11 eyes) improved from 382.2±98.4 (baseline) to 195.5±38.9 microns (1st year). After a mean follow-up of 40.7±25 months anti-TNFα drugs was well tolerated in most cases. The most important side effects were pulmonary TBC (n=1), herpes zoster (n=2), urinary tract infection (n=3) and elevation of liver enzymes during treatment (n=2). Conclusions: Anti-TNFα therapy seems effective and relatively safe in refractory uveitis. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3369